KAJIAN USAHATANI PADI SAWAH DI DAERAH IRIGASI KAYAWU KECAMATAN TOMOHON UTARA KOTA TOMOHON (PERBANDINGAN USAHATANI DI BAGIAN HULU DENGAN DI BAGIAN HILIR) - Vellycia Triutarie Datu Patandianan; Eyverson ., Ruauw; Gene Henfried Meyer Kapantow (AGRI-SOSIOEKONOMI, 2021)
This study aims to determine whether there are differences in productivity and income of lowland rice farming with irrigation systems in the upstream and downstream irrigation systems. This research was conducted from May to August 2019. The sample determination was carried out by simple random sampling. This research used qualitative and quantitative analysis, the resulting data is analyzed using the average difference test (t test). The results of the research were: (1) The average income obtained by lowland rice farmers was 11,737,459 per hectare, the average income obtained by downstream rice farmers was 7,315,001 per hectare. From the results of data processing with the t-test gives a p-value of 0.005. So at Î± = 0.05 H0 is rejected. (2) The average production obtained by lowland rice farmers in the upstream section is 2,235 per hectare, the average production obtained by downstream rice farmers is 2,054 per production. The results of data processing with the t-test gave a p-value of 0.004. So at Î± = 0.05 H0 is rejected. From the research results, it can be concluded that the income and productivity of lowland rice farming in the upstream part is higher than that of lowland rice farming.